2020
DOI: 10.3345/cep.2019.01536
|View full text |Cite
|
Sign up to set email alerts
|

Influence of subclinical hypothyroidism on metabolic parameters in obese children and adolescents

Abstract: Background: Subclinical hypothyroidism (SH) is a common condition in obese children. However, its effect on glucose and lipid metabolism in obese children remains controversial.Purpose: The present study aimed to investigate the association between SH and metabolic parameters.Methods: A total of 215 obese children and adolescents aged 6–18 years were included in this retrospective cross-sectional study. The patients’ anthropometric measurements such as thyrotropin (TSH), free thyroxine (fT4), fasting plasma gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
2
10
1
2
Order By: Relevance
“…En analogía con el estudio de Jin (24), no se encontró correlación de la TSH en suero con resistencia a la insulina, en contraste con otros reportes (27,28). Los escolares con obesidad y T4 libre baja se correlaciona- ron significativamente con hiperinsulinismo y presentaron promedios mayores de HO-MA1-IR.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En analogía con el estudio de Jin (24), no se encontró correlación de la TSH en suero con resistencia a la insulina, en contraste con otros reportes (27,28). Los escolares con obesidad y T4 libre baja se correlaciona- ron significativamente con hiperinsulinismo y presentaron promedios mayores de HO-MA1-IR.…”
Section: Discussionunclassified
“…Los valores de hormonas tiroideas no presentaron diferencias, en relación con el grado de maduración sexual y sexo, al igual como lo han señalado algunos autores ( 25,27,32) . Todos los escolares con TSH elevada eran prepúberes.…”
Section: Discussionunclassified
“…The current study revealed higher incidence of subclinical hypothyroidism in children with obesity (36%) with significant association between TSH level and BMI. Despite of the significant increased frequency of subclinical hypothyroidism in children with obesity, there is variation in the prevalence between studies which ranged from 7 to 36% [12]. This variation could attribute to different ethnic groups and the contributing effect of hyperlipidemia and metabolic syndrome on the development of subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric as in adults, thyrotropin >10 mIU/L is potentially indicative of overt hypothyroidism. Subclinical hypothyroidism is identified as isolated raised TSH (>4.5 mIU/L but <10 mIU/L) without clinical symptoms, thyroid antibodies, goiter, or associated thyroidal illness [12]. Obese children were classified according to the level of TSH into obese children with and without subclinical hypothyroidism.…”
Section: Thyroid Function Testmentioning
confidence: 99%
“…Subclinical hypothyroidism is associated with obesity in paediatric subjects [23,24]. A retrospective study identified subclinical hypothyroidism (normal FT4, TSH 5-10 mIU/L) in 36% of a population of 215 obese children and adolescents [25]. Subjects with vs. without subclinical hypothyroidism were more insulin resistant and showed signs of atherogenic dyslipidaemia (low HDL-C, high triglycerides), but BMI was similar.…”
Section: Outcomes In Children With Subclinical Hypothyroidismmentioning
confidence: 99%